Nutritional, antioxidant, and sensory properties of innovative onion pie produced from whole wheat flour, carob beans flour, onion, scallions, and roasted Seaweeds - F. M. Ali, Rehab; M. El-Anany, Ayman (Italian Journal of Food Science, 2024)
Snack foods have experienced substantial growth in consumption globally, appealing to various age groups and becoming a significant segment of the food industry. The current investigation aimed to assess the nutritional, antioxidant, and sensory characteristics of an unconventional pie prepared from brown wheat flour(BWF), carob bean flour (CBF), onion, scallions, and roasted seaweeds. Chemical composition, minerals content, functional properties, total phenolics, total flavonoids, and antioxidants activity (DPPH), and phenolic profile of CBF, BWF, and binary combinations were evaluated. Five pies using different formulas (CGR0, CGR1, CGR2, CGR3, CGR4, and CGR5) were developed, where CGR0 serving as the control sample with 100% BWF. The other formulations (CGR1–CGR5) are binary combinations of BWF and CBF at various ratios (90:10, 80:20, 70:30, 60:40, and 50:50%). The onion pie samples were assayed for proximate composition, minerals, and sensory properties. CBF is rich in dietary fibers, with a content of 12.73%, substantial ash (4.79%), and carbohydrates (74.36%). Blending BWF with CBF significantly enhances the functional properties of the mixture, as indicated by improved WAC, AOC, EA, and FC compared to BWF. The addition of CBF into BWF in produced pie recipes led to significant increases in Fat, fiber, and ash. Additionally, substituting BWF with CBF in pie samples led to substantial decreases in carbohydrate content. The highest content of micro- and macro-elements was found in CGR5 samples, whereas the lowest was found in control samples CGR0. The results found that incorporating CBF into onion pie samples at levels between 10% to 40% can positively impact the sensory acceptability of the produced pie samples.